Pengaruh Pendapatan Bagi Hasil Deposito Mudharabah Terhadap Roa ( Study Empiris pada Bank BNI Syariah Tahun 2013-2015) - Widya Rahmadani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2019)
The level of profit sharing provided by Islamic banks is one of the attractions of the public to save funds in Islamic bank products, but the rate of return for Islamic banks is also still attractive in conventional banks. Because still agreeing to conventional bank interest rates makes people still think about Islamic banks the same as conventional banks. Mudharabah BNI Syariah Bank. The population used is the quarterly financial statements of all BNI Syariah banks in 2013-2015. In this study a simple regression analysis using 16.0 software was used, the variable used in this study was income for mudharabah results as an independent variable and Return On Assets (ROA) as the dependent variable. Most of these results show significant results from ROA.